Analisis Penentuan Ujrah Produk Gadai Emas di Perbankan Syariah (BSI Kantor Cabang Bangkalan) - Nur Aini (Journal of Islamic Banking, 2024)
Through fatwa number: 25/DSN-MUI/III/2002 issued by the National Sharia Council and the Indonesian Ulema Council on June 26, 2002, it is stated that the costs of maintaining and storing the collateral (Marhun) should not be determined based on the loan amount. However, in practice, the ujrah (rental fee) charged to customers changes according to the amount of the loan requested. This research aims to analyze the determination of ujrah on gold pawn products available in Islamic banking. The type of research used in this study is qualitative research, which analyzes and describes how the ujrah for gold pawn products in Islamic banking is actually determined. Data collection techniques employed include case study and interview methods. Data analysis uses qualitative data analysis, which involves systematically searching and organizing the data obtained from case study, drawing conclusions, and finally conducting a data credibility test. This study concludes that the determination of ujrah for gold pawn products in Islamic banking, specifically at BSI Syariah, is based on the loan amount. The ujrah costs for pawn loans are as follows: for loans of IDR 500,000 – IDR 20,000,000: 1.8% of financing; for loans of IDR 20,000,000 – IDR 100,000,000: 1.5% of financing; for loans exceeding IDR 100,000,000: 1.1% of financing. The larger the loan amount, the smaller the ujrah that the customer has to pay.